1998
DOI: 10.1115/1.2818177
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Jet Fuel Oxidation

Abstract: A quartz crystal microbalance (QCM)/Parr bomb system with a headspace oxygen sensor is used to measure oxidation and deposition during thermal oxidative stressing of jet fuel. The advantages of the oxygen sensor technique in monitoring fuel oxidation is demonstrated. Simultaneous measurement of deposition using the QCM shows a strong correlation between oxidation and deposition in jet fuels. Studies performed over the temperature range 140 to 180°C show that surface deposition peaks at an intermediate temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Both antioxidants extend the induction time, but the final oxidation rate remains the same. Zabarnick and Whitacre observed similar behavior for BHT in a fast oxidizing fuel stressed in the QCM . They showed that BHT slowed the oxidation rate until it was consumed, then the autoxidation continued at a more rapid rate.…”
Section: Resultsmentioning
confidence: 79%
“…Both antioxidants extend the induction time, but the final oxidation rate remains the same. Zabarnick and Whitacre observed similar behavior for BHT in a fast oxidizing fuel stressed in the QCM . They showed that BHT slowed the oxidation rate until it was consumed, then the autoxidation continued at a more rapid rate.…”
Section: Resultsmentioning
confidence: 79%
“…The initial slow oxidation during the first 10 h is due to the interception of alkylperoxy radicals by BHT. Previous work in our laboratory has shown that the subsequent rapid oxidation, which occurs here at 10 h, is due to the consumption of BHT below some critical concentration . The most striking observation from Figure is the extremely slow oxidation which occurs when both BHT and hexyl sulfide are present.…”
Section: Resultsmentioning
confidence: 49%
“…Fuel oxidation and deposition characteristics were evaluated in the quartz crystal microbalance (QCM) Parr bomb system that has been described in detail previously. , Most fuel oxidation tests were run at 140 °C and 1 atm of air initial pressure. The reactor is heated with a clamp-on band heater, and its temperature is controlled by a PID controller via a thermocouple immersed in the fuel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hindered phenol and amine antioxidants were evaluated. 6 We studied various aspects of jet fuel oxidation behavior, including the correlation between oxidation and deposition, the temperature dependence of oxidation and deposition, and studies of peroxy radical intercepting antioxidants and metal deactivator additives (Zabarnick and Whitacre, 1998). These studies showed a strong correlation between oxygen consumption and deposition, demonstrating the direct relationship between these phenomena.…”
Section: High Heat Sink Fuel Studiesmentioning
confidence: 99%